Insulin Confers Differing Effects on Neurite Outgrowth in Separate Populations of Cultured Dorsal Root Ganglion Neurons: The Role of the Insulin Receptor - Lázár, Bence András; Jancsó, Gábor; Pálvölgyi, Laura; Dobos, Ildikó; Nagy, István; Sántha, Péter (Frontiers in Neuroscience, 2018)
Apart from its pivotal role in the regulation of carbohydrate metabolism, insulin exerts important neurotrophic and neuromodulator effects on dorsal root ganglion (DRG) neurons. The neurite outgrowth-promoting effect is one of the salient features of insulin’s action on cultured DRG neurons. Although it has been established that a significant population of DRG neurons express the insulin receptor (InsR), the significance of InsR expression and the chemical phenotype of DRG neurons in relation to the neurite outgrowth-promoting effect of insulin has not been studied. Therefore, in this study by using immunohistochemical and quantitative stereological methods we evaluated the effect of insulin on neurite outgrowth of DRG neurons of different chemical phenotypes which express or lack the InsR. Insulin, at a concentration of 10 nM, significantly increased the total neurite length, the length of the longest neurite and the number of branch points of cultured DRG neurons as compared to neurons cultured in control medium or in the presence of 1 M insulin (p < 0.05). In both the control and the insulin exposed cultures, 43% of neurons displayed InsR-immunoreactivity. The proportions of transient receptor potential vanilloid type 1 receptor (TRPV1)-immunoreactive (IR), calcitonin gene-related peptide (CGRP)-IR and Bandeiraea simplicifolia isolectin B4 (IB4)-binding neurons amounted to 61%, 57% and 31% of DRG neurons IR for the InsR. Of the IB4-positive population only neurons expressing the InsR were responsive to insulin. In contrast, TRPV1-IR nociceptive and CGRP-IR peptidergic neurons showed increased tendency for neurite outgrowth which was further enhanced by insulin. However, the responsiveness of DRG neurons expressing the InsR has been superior to populations of DRG neurons which lack this receptor. The findings also revealed that besides the expression of the InsR, inherent properties of peptidergic, but not nonpeptidergic nociceptive neurons may also significantly contribute to the mechanisms of neurite outgrowth of DRG neurons. These observations suggest distinct regenerative propensity for differing populations of DRG neurons which is significantly affected through insulin receptor signaling.